PENERAPAN MODEL EDUKASI ASI DENGAN VISUALISASI PRAKTIK PADA IBU HAMIL - Risna Dewi Yanti; Sri Mulyati; Eva Sri Rahayu (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
The exclusive coverage of ASI in Indonesia is 42%. Various programs and strategies have been developed by the government to disseminate the importance of exclusive breastfeeding to mothers and families. One of them is through a class of pregnant women at posyandu and puskesmas. However, it is not enough to increase the readiness of mothers to breastfeed their babies. Interesting media and methods are needed and have a long memory retention in the delivery of information about ASI. One of them is the practice visualization method, which is conveying information through a combination of lectures, videos, pictures, symbols, analogies and practice items. The activity is an activity in providing information about breastfeeding readiness to pregnant women The activity is designed to be carried out within a period of 12 months. It starts with preparation, pre-test the preliminary knowledge of pregnant women about breastfeeding, giving ASI material with a visualization of practice for 7 activities. The evaluation of the activity in the form of a pre-test is carried out from the first meeting. Furthermore, in the final stage, a post-test will be conducted to determine the extent of the success of community service activities that have been carried out.